(untitled) (Damu Journal of Sport Sciences, 2025)
The research aims to prepare anaerobic exercises for young football players, to identify the effect of anaerobic exercises on the level of some physiological indicators (CPK, LDH, LA) for football players under 23 years old. The researcher used the experimental method with the experimental group as it is the most appropriate method to address the research problem. The research community consisted of football players under (23 years old) in Diyala Governorate, distributed among (4) clubs, with (72) players, distributed among the clubs (Diyala, Al-Khalis, Al-Muqdadiya, Al-Shaheed Arkan). The research sample was chosen randomly by lottery, and they were Al-Muqdadiya Sports Club players, numbering (22) players, representing (30.55%) of the original community. The researcher concluded that anaerobic exercises achieved their effectiveness, as the experimental group showed a tangible development compared to the control group, which enhances the effectiveness of anaerobic exercises directed at improving the variables (CPK, LDH, LA). The exercises also demonstrated a significant improvement in blood enzymes (CPK, The researchers also recommend focusing on anaerobic exercise aimed at improving enzymes (CPK, LDH, LA), given their role in increasing muscle endurance and improving recovery after training. They also recommend conducting periodic assessments of physiological, physical, and skill variables during the training season to monitor progress and adapt the training load to suit the players' responses. Anaerobic exercise should be adopted as an essential part of the training program for under-23 football players, given the positive results it has shown on physiological variables.